Protection of Plantation from Wild Animals Using Wireless Sensor Network - T. , Manikandan; V. , Nandalal; J.L. , Mazher Iqbal; S. , Joshua Kumaresan; S., Karthikeyan (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of the project is to design a protection system for the farmland monitoring from wild animals using a wireless sensor network. In the current scenario, many farmers face the crisis of a decrease in the crop yield. This may be due to various problems; one such problem is the intrusion of animals in the farmland and destroying the plantation. So, to address this major issue, an enhanced system is created to protect the farm from disturbance by wild animals. The system also ensures that it is not hazardous to animals and humans. In this proposed work, sensors such as a PIR sensor (passive infrared sensor) and a vibration sensor are used. The PIR sensors are fixed along the boundary of the farm, which detects the motion of the object, and vibration sensors are laid on the land a few meters outside the farm boundary to sense the footsteps of the animal trying to enter the farm. Whenever some animal passes near the farm area, the PIR sensor detects the motion, and the microcontroller displays motion detected in the display unit of the farm. If the animal is still approaching the farm, the vibration sensor senses the foot vibrations, and the sensor value is given to the microcontroller. An alert message is displayed in the farm display unit, and the farm manager is also notified by alert message using the GSM module that some animal tried to enter the farm area.